Nonlinear wood anomalies in the reflectivity of layered superconductors - Apostolov, S.S.; Maizelis, Z.A.; Sorokina, M.A.; Yampol’skii, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We study theoretically the excitation of the nonlinear surface Josephson plasma waves in slabs of layered superconductors by the incident plane waves using the prism method in the Otto configuration. The bilateral, symmetrical with respect to magnetic field, excitation is considered. The excitation leads to the resonant suppression of the specular reflection, i.e., to the Wood anomalies. Due to the nonlinearity, the reflectivity resonantly depends not only on the wave frequency ω and the incident angle θ, but on the wave amplitude h as well. We show that the total suppression of the reflectivity can be attained by the appropriate choice of ω, θ, h, and other parameters of the problem. The results of the analytical calculations are supported by numerical simulations.